Economic integration and the evolution of trade: a geometric interpretation of trade measures - Abdul Karim, Mohd Azhar; Elliott, Robert J. R. (Center for International Economics, Sejong Institution, 2004)
The increase in global trade and the ongoing erosion of trade barriers makes the analysis of trade patterns one of the key areas in international economics. Much of the post-war expansion of trade took the form of intra-industry trade (IIT). This paper presents a simple geometric tool to analyse trade patterns specifically inter and intra-industry trade and the compatibility between levels and measures of IIT. The applicability our methodology is demonstrated using the UKs trade experience during the critical period of EU integration 1988-1997.